"No One Will Do This For Us" The Linguistic and Cultural Practices of Young Activists Representing European Linguistic Minorities - Dolowy-Rybinska, Nicole (Sprach- und Kulturkontakte in Europas Mitte, 2020)
This book presents a portrait of actively engaged young people representing four linguistic minorities in Europe: the Kashubs (in Poland), the Upper Sorbs (in Germany), the Bretons (in France), and the Welsh (in the United Kingdom). In numerous statements cited in the book, drawn from interviews conducted by the author, young people speak for themselves and serve as guides to their minority cultures. They draw attention to the difficulties and challenges they encounter in their day-to-day life and activism. Based on their statements, the book examines the sociolinguistic situation of each of the minorities, the prevailing linguistic ideologies and the role of minority education; it also distinguishes different types of minority language speakers. The analysis focuses on the cultural and identity-forming practices of young people in the context of different forms of community life and their different pathways to becoming engaged representing their cultures and languages.